HEALTHCARE MANAGEMENT global perspectives. - Gillies, Alan. ([S.l.] : ROUTLEDGE, 2025)
Healthcare Management takes a look at international perspectives in healthcare management and the way regional priorities, national income, and social factors are crucial to effective healthcare services. Readers are provided the skills to address issues and solve problems as a healthcare manager by understanding and appreciating the complex interrelationships of global health provision. The book compares and contrasts different healthcare systems, examining the role of policymaking, health financing, healthcare beyond hospitals, leadership, risk management, and quality. A range of international case studies provide the opportunity to see how different theories work in practice. This comprehensive book is suitable for students and professionals undertaking healthcare management courses.
Keywords: BUSINESS & ECONOMICS / Management; Health services administration; Medical policy; Personnel management